Temperature and Humidity Controlling System for Baby Incubator - Latif, Abdul; Agus Widodo, Hendro; Andri Atmoko, Rachmad; Nguyen Phong, Thanh; T.Helmy, Elsayed (Journal of Robotics and Control (JRC), 2021)
Baby incubator is very important to keep the newborn’s body temperature especially for premature babies. The research aimed to design a baby incubator with controlled temperature and humidity. The incubator is designed to have a length of 60 cm, a width of 40 cm, and a height of 30 cm. System of baby incubator will automatically turn on or turn off the fan and or heating in accordance with the normal range of temperature and humidity in the incubator. The normal limits of temperature used is 33°C to 35°C. While the normal limits of air humidity in the incubator used is between 40% and 60%. Data acquisition system consists of temperature and humidity sensor, microcontroller ATmega8535, fan, heater, and LCD. LCD is used to display the results of measurements of temperature and humidity. Heater is used to regulate the temperature in the incubator. While fan is used to regulate the humidity in the incubator. Test results show that the heater will turn on if the temperature is below the limits of 33°C. While the fan will turn on if the humidity is above 60%